Prediction of functional recovery by cardiac magnetic resonance feature tracking imaging in first time ST-elevation myocardial infarction. Comparison to infarct size and transmurality by late gadolinium enhancement - Buß, Sebastian Johannes; Krautz, Birigt; Hofmann, Nina; Sander, Yannick; Rust, Lukas; Giusca, Sorin; Galuschky, Christian; Seitz, Sebastian; Giannitsis, Evangelos; Pleger, Sven Torsten; Raake, Philip; Most, Patrick; et al. (International journal of cardiology, 2015)
Purpose - To investigate whether myocardial deformation imaging, assessed by feature tracking cardiac magnetic resonance (FTI-CMR), would allow objective quantification of myocardial strain and estimation of functional recovery in patients with first time ST-elevation myocardial infarction (STEMI). - Methods - Cardiac magnetic resonance (CMR) imaging was performed in 74 consecutive patients 2-4days after successfully reperfused STEMI, using a 1.5T CMR scanner (Philips Achieva). Peak systolic circumferential and longitudinal strains were measured using the FTI applied to SSFP cine sequences and were compared to infarct size, determined by late gadolinium enhancement (LGE). Follow-up CMR at 6months was performed in order to assess residual ejection fraction, which deemed as the reference standard for the estimation of functional recovery. - Results - During the follow-up period 53 of 74 (72%) patients exhibited preserved residual ejection fraction ≥50%. A cut-off value of −19.3% for global circumferential strain identified patients with preserved ejection fraction ≥50% at follow-up with sensitivity of 76% and specificity of 85% (AUC=0.86, 95% CI=0.75-0.93, p<0.001), which was superior to that provided by longitudinal strain (ΔAUC=0.13, SE=0.05, z-statistic=2.5, p=0.01), and non-inferior to that provided by LGE (ΔAUC=0.07, p=NS). Multivariate analysis showed that global circumferential strain and LGE exhibited independent value for the prediction of preserved LV-function, surpassing that provided by age, diabetes and baseline ejection fraction (HR=1.4, 95% CI=1.0-1.9 and HR=1.4, 95% CI=1.1-1.7, respectively, p<0.05 for both). - Conclusions - Estimation of circumferential strain by FTI provides objective assessment of infarct size without the need for contrast agent administration and estimation of functional recovery with non-inferior accuracy compared to that provided by LGE.
Gesehen am 27.10.2020